2019
DOI: 10.1038/s41598-019-46691-x
|View full text |Cite|
|
Sign up to set email alerts
|

Spring constant and sensitivity calibration of FluidFM micropipette cantilevers for force spectroscopy measurements

Abstract: The fluidic force microscope (FluidFM) can be considered as the nanofluidic extension of the atomic force microscope (AFM). This novel instrument facilitates the experimental procedure and data acquisition of force spectroscopy (FS) and is also used for the determination of single-cell adhesion forces (SCFS) and elasticity. FluidFM uses special probes with an integrated nanochannel inside the cantilevers supported by parallel rows of pillars. However, little is known about how the properties of these hollow ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 34 publications
0
27
0
Order By: Relevance
“…The adhesion force curves were calculated by multiplying the differential signal of the PSD (measured in mV) with the sensitivity then with the spring constant to convert the distance values to force. The recorded force curves were then evaluated according to the standard protocol in literature 85,86 .…”
Section: Robotic Fluidic Force Microscopy and Calibration Of Probes mentioning
confidence: 99%
“…The adhesion force curves were calculated by multiplying the differential signal of the PSD (measured in mV) with the sensitivity then with the spring constant to convert the distance values to force. The recorded force curves were then evaluated according to the standard protocol in literature 85,86 .…”
Section: Robotic Fluidic Force Microscopy and Calibration Of Probes mentioning
confidence: 99%
“…Nagy et al presented a table showing a possible error in the SCFS data obtained from FluidFM experiments. [23] This may result from an improper determination of the spring constant and the sensitivity of the cantilever. They proposed a calibration strategy and an optimal laser position to reduce the error in calibration.…”
Section: Fluidfm Set-up and Cantilever Preparationmentioning
confidence: 99%
“…[30] C. albicans are prone to adhere to hydrophobic surfaces (e.g., coated with DDP) through non-specific hydrophobic interactions. SCFS was performed on the cells incubated at different times (up to 9 h) on a moderately hydrophobic surface (an ITO surface coated with a mixture of DDP and DDP-OH) at different temperatures (23,30, and 37 °C). It was found that incubation at a lower temperature (23 °C) and for a longer time period results in higher adhesion forces.…”
Section: Microorganismsmentioning
confidence: 99%
“…There are several limits for the detection of quantitative and detailed information on the interactions between stem cells and biomaterials because they occur in the nanoscale and in physiological conditions. In order to overcome these limitations and to find a better method for a quantitative detection, experiments of single-cell force spectroscopy (SCFS) have been performed, using micropipettes [170], magnetic-[171] or optical tweezers [172]. However, these methods are characterized by a low force resolution (from 10pN to 1nN).…”
Section: Biomaterials and Stem Cells Interactionsmentioning
confidence: 99%